Assessment of the water sorption properties of several microcrystalline celluloses (2011)
ABSTRACT: This paper compares the water sorption behavior of commercial microcrystalline celluloses with those of cellulose II materials using several nonlinear models. Aqueous dispersions of cellulose II were spray-dried employing an inlet drying air temperature of 195 °C; atomizing air pressure of 1.0 kg-f/cm2; drying air flow-rate of 0.44 m3/min; feed flow-rate of 2.0 mL/min and nozzle diameter of 0.7 mm. Cellulose II samples were also spheronized in a Fuji Paudal spheronizer for 10 min at 1000 rpm. Products were analyzed for water sorption on a VTI® symmetrical gravimetric analyzer in triplicates. The Guggenheim-Anderson-de Boer (GAB), Hailwood-Horrobin (HH), Generalized D’Arcy and Watt (GDW) and Young and Nelson (YN) models were employed for the data analysis. Most of the sorption isotherms exhibited a type II sigmoid shape. Celphere®203, presented a type III isotherm and showed the highest monolayer capacity (m0 of 0.15 g water/g cellulose) and the lowest monolayer energy constant (C=1.0) given by the GAB model. The GDW model indicated that the monolayer capacity (m0) and the fraction of sorption sites available for multilayer sorption (w) were the highest for Celphere®203 (1.0 g/g cellulose and 1.0, respectively). The HH model indicated that Celphere®203 had the highest sorption capacity (W of 3.0 g/g sorption site). The YN model showed that this material had the largest water uptake by absorption into the core of the particles. Celphere®203 and SPCII were the most hydrophilic materials. Neither polymorphic form, nor silicification, was responsible for the difference in the hydrophilic properties of cellulose.